Skandinaviens Ureinwohner und die Delikatessen der Wikinger ... : Skandinaviens Ureinwohner und die Delikatessen der Wikinger ... - Lozzi Gallo, Lorenzo (Rhesis. International Journal of Linguistics, Philology and Literature, 2021)
With the expansion of the Germanic tribes from the Southernmost part of Scandinavia, it seems that the natives gradually retreated to the less hospitable areas in the North and on the mountains, less attractive for the newcomers due to a rigid climate and scarcity of arable land. Being predominantly hunters-gatherers, natives could hardly grow cereals in their areas of residence and therefore they may have relied entirely on trade with Vikings to acquire beer or bread. Some kinds of meat (pork, beef, mutton) were equally exotic to these tribes who had specialized in hunting and herding reindeer. About dairy products, reindeer milk is far less suited to be processed than cow milk, there is only one kind of traditional cheese. The diet of the natives must have been quite monotone (but for the short arctic summer) and Viking gastronomy must have been a more than welcome change in their usual nourishment – when they managed to get some. Even though the natives were often in contact with Vikings, they were also ... : Rhesis. International Journal of Linguistics, Philology and Literature, V. 12 N. 1 (2021): Linguistics and Philology ...